NOVEDOSOS RESTOS DE NEOEPIBLEMIDAE (RODENTIA, HYSTRICOGNATHI) DEL MIOCENO TARDIO DE VENEZUELA INFERENCIAS PALEOAMBIENTALES (Ameghiniana, 2013)
The first known associated upper and lower molars of a species of the poorly known "caviomorph" rodent family Neoepiblemidae are described. These remains were collected in the Urumaco Formation, Venezuela, probably representing the Huayquerian land-rnammal Age (late Miocene). Based on the upper and lower cheek-teeth of these giant rodents (the largest ones ever known) found in the Late Miocene sediments of Argentina three genera were recognized: Neoepiblema Ameghino, 1889; Phoberomys Kraglievieh, 1926 and Dabbenea Kraglievieh, 1926. The remains here described proves that the upper cheek-teeth on which the specie type of Dabbenea, D. insolita was based, pertained to animals co-generic with Phoberomys, whose type species P. burmeisteri was based on lower molars. Thus, according to the International Code of Zoological Nomenclature (Art. 23) Dabbenea, Kraglievich, 1926 is the junior synonym of Phoberomys Kraglievich, 1926. The numerous as well as varied vertebrate remains recorded in the Urumaco Formation led to the conclusion that those sediments were deposited throughout floodplains, developed near coastal lagoons, including extended grasslands between lentic and lotic waterbodies.